Effects of LC50 chlorantraniliprole using different application methods on adult Spodoptera exigua and across generations - Wang, Lin; Zhang, Zilu; Askar, Mofeed; Li, Yaohai; Yang, Ci; Gesang, Quzhen; Su, Honghua (Frontiers in Agronomy, 2025)
IntroductionThe beet armyworm Spodoptera exigua (Hübner, 1808)(Lepidoptera: Noctuidae) represents a cosmopolitan polyphagous lepidopteran pest of paramount agricultural significance, necessitating strategic intervention during the reproductive-competent imaginal stage to mitigate population amplification and geographic dissemination. Chlorantraniliprole is an anthranilic diamide insecticide with high selectivity for arthropod ryanodine receptors (RyR).MethodsThis investigation systematically evaluated median lethal (LC₅₀) ramifications of chlorantraniliprole upon adult S. exigua demographic performance and transgenerational fitness consequences utilizing three distinct administration modalities: oral consumption via chlorantraniliprole-fortified sucrose solution, pronotal microdroplet deposition, and pedal contact exposure.ResultsPronounced inter-treatment variability was documented across multiple life-history parameters. Oral ingestion of the toxic nutrient matrix dramatically curtailed adult longevity by 6.067 days and median lethally diminished reproductive output by 309.3 eggs, while concurrently suppressing parental egg viability by 52.01% relative to untreated controls. Pronotal topical application demonstrated negligible effects on parental demographic metrics but significantly compromised F₁ egg hatchability by 42.93%. Tarsal contact exposure exerted the most profound transgenerational perturbations, prolonging F₁ larval developmental duration by 2.969 days, augmenting pupal biomass by 0.008 g, and extending pupal metamorphic chronometry by 17.6 hours. Additionally, this treatment modality reduced F₁ egg viability by 42.83%, decreased F₁ fecundity by 411.9 eggs, suppressed imaginal emergence rates by 30.8%, and elevated developmental malformation incidence by 5.28%.DiscussionThese findings demonstrate that delivery methodology fundamentally modulates chlorantraniliprole's demographic impact trajectory, with oral administration optimizing parental suppression while pedal contact maximizing transgenerational attenuation of S. exigua population dynamics. Future research should explore developing chlorantraniliprole-laced food attractants and advancing pest control timing to enhance efficacy.